2012
DOI: 10.1186/1532-429x-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of distribution and evolution of Mechanical dyssynchrony in a porcine model of myocardial infarction by cardiovascular magnetic resonance

Abstract: BackgroundWe sought to investigate the relationship between infarct and dyssynchrony post- myocardial infarct (MI), in a porcine model. Mechanical dyssynchrony post-MI is associated with left ventricular (LV) remodeling and increased mortality.MethodsCine, gadolinium-contrast, and tagged cardiovascular magnetic resonance (CMR) were performed pre-MI, 9 ± 2 days (early post-MI), and 33 ± 10 days (late post-MI) post-MI in 6 pigs to characterize cardiac morphology, location and extent of MI, and regional mechanics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 38 publications
10
62
2
Order By: Relevance
“…The values of observer variability characteristics obtained in this study are well in line with previous reports [27, 3538]. However, some studies from specialized centers achieved consistently higher inter- and intra-observer variability, with ICCs > 0.99 [27, 29, 39]. This difference might be explained by the limited clinical experience of our readers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The values of observer variability characteristics obtained in this study are well in line with previous reports [27, 3538]. However, some studies from specialized centers achieved consistently higher inter- and intra-observer variability, with ICCs > 0.99 [27, 29, 39]. This difference might be explained by the limited clinical experience of our readers.…”
Section: Discussionsupporting
confidence: 91%
“…For MOLLI, ECV-values between 0.25 and 0.27 have been reported at 1.5T [9, 15, 26] and between 0.26 and 0.28 at 3T [2629]. Furthermore, the slight increase in ECV-values between the two post-contrast time points has been previously observed with MOLLI at 3T [29], and the ECV deviation between the two time points is in agreement with previous reports (0.258–0.272 for times between 10 and 25 min [28]. Close agreement of SAPPHIRE ECV-values are obtained with a previous study at 1.5T (ECV: 0.20 [9]).…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 10–20% of the patients with critically severe AS do not have LVH. A recent study showed that the extent of LVH did not necessarily correlate with the severity of AS [9]. This evidence suggested that the pathogenesis and regulation of LVH was complicated and not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…After undersampling the k-space data, coil compression with principal component analysis [16, 17] was performed on the measured k-space data and the data was compressed into 4 virtual coils. Each coil was reconstructed separately and then the results combined with the square root of sum of squares.…”
Section: Methodsmentioning
confidence: 99%
“…Each coil was reconstructed separately and then the results combined with the square root of sum of squares. As discussed in [16, 17], coil compression reduces the total number of coils required to reconstruct the image and hence reduces the reconstruction time. Experiments were performed to see how many virtual coils are necessary to reconstruct images without any loss of image quality due to coil compression.…”
Section: Methodsmentioning
confidence: 99%